The effect of Cu (I) and Cu (II) ions' low concentrations on growth, biohydrogen production and the FoF1-ATPase activity of Rhodobacter sphaeroides. (15th October 2016) - Hakobyan, Lilit; Sargsyan, Harutyun; Gabrielyan, Lilit; Trchounian, Armen
Abstract: Various metal ions play a key role in growth and biohydrogen (H2 ) production by phototrophic bacteria through incorporation into or stimulation of the responsible enzymes and/or related metabolic pathways. This study shows, that Cu (I) ions, at low concentration (<5 μM), suppressed the growth of Rhodobacter sphaeroides strain MDC6521, isolated from mineral springs in Armenia, but enhanced the H2 yield by this bacterium. In contrast, Cu (II) ions with the same concentrations inhibited H2 yield. These ions also affected the medium redox potential during R. sphaeroides growth. N, N ′-dicyclohexylcarbodiimide-sensitive ATPase activity of R. sphaeroides membrane vesicles was increased in the presence of both ions. Cu ions at low concentrations are suggested to affect biohydrogen production pathways or responsible enzymes in R. sphaeroides, proton Fo F1 -ATPase of which could be a target for these ions. Highlights: Cu ions at low concentrations (<5 μM) delayed R. sphaeroides growth inhibition. Cu ions affected H2 production during photofermentation. The F0 F1 -ATPase mediates the effects of Cu ions on H2 production.